2014
DOI: 10.5713/ajas.2013.13261
|View full text |Cite
|
Sign up to set email alerts
|

Multicarbohydrase Enzymes for Non-ruminants

Abstract: The first purpose of this review is to outline some of the background information necessary to understand the mechanisms of action of fibre-degrading enzymes in non-ruminants. Secondly, the well-known and understood mechanisms are described, i) eliminating the nutrient encapsulating effect of the cell wall and ii) ameliorating viscosity problems associated with certain Non Starch Polysaccharides, particularly arabinoxylans and β-glucans. A third, indirect mechanism is then discussed: the activity of such enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 85 publications
0
75
0
Order By: Relevance
“…However, broilers subjected to the β-manananase + MOS interaction can worsen their performance, demonstrating a possible antagonism between substances or changes in villus in the absorptive portion of the chickens' gastrointestinal tract (O'NEILL et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, broilers subjected to the β-manananase + MOS interaction can worsen their performance, demonstrating a possible antagonism between substances or changes in villus in the absorptive portion of the chickens' gastrointestinal tract (O'NEILL et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Endogenous enzymes produced by poultry and swine cannot hydrolyze the NSPs contained in cereals (OPALINSKI et al, 2010). In poultry, only the amylase enzyme produced by the pancreas can hydrolyze starch into smaller units that can be absorbed; therefore, the presence of exogenous enzymes is needed (O'NEILL et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The proposal of application of exogenous enzymes in poultry nutrition was initially suggested almost 100 years ago (20), however, the prohibitive cost did not allow their application in animal nutrition until many decades later (21). Xylanases and βglucanases were pioneer commercial feed enzymes to deal with problematic viscous feedstuffs such as barley and wheat (22)(23)(24)(25).…”
Section: Feed Enzymesmentioning
confidence: 99%
“…Xylanases and βglucanases were pioneer commercial feed enzymes to deal with problematic viscous feedstuffs such as barley and wheat (22)(23)(24)(25). Early experimentations showed that supplementation of these enzymes in diets rich in viscous feedstuffs improved digestibility, growth performance and reduced feed costs (21)(22)(23). These studies helped scientists to understand the modes of action and stimulated further research and development efforts to innovate novel activities targeting specific substrates and stabilized to withstand the rigors of feed processing and gastrointestinal conditions (26).…”
Section: Feed Enzymesmentioning
confidence: 99%
“…They are converted by microflora to volatile fatty acids, which are absorbed and are a source of energy; in addition they lower the pH, which inhibit the proliferation of coliform bacteria. At the same time, the formation of butyric acid promotes the growth of brush border microvilli [6]. At the same time, the population of microorganism's decreases, which leads to a decrease in their consumption of nutrients, was increasing their availability to the animal.…”
Section: Discussionmentioning
confidence: 99%